Analysis of User Satisfaction of Fintech OVO Using Delone and Mclean Information System Success Model in Denpasar City - Estiyanti, Ni Made; Berliana, Ni Kadek Sinta; Alam, Helmy Shakh (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims to find out how the influence of information quality, system quality, service quality, and security, on user satisfaction in the OVO application in Denpasar. This study uses a quantitative approach, data processing methods using SEM-PLS. used is SmartPLS 3.0. The population of this study are users of the OVO digital payment system in Denpasar. The sample was determined based on cluster sampling technique and random sampling, with a sample of 96 respondents. The results of this study prove that of the 10 hypotheses made there are 7 hypotheses that are accepted, namely the relationship between system quality and use, the relationship between system quality and user satisfaction, information quality and user satisfaction, service quality and use, service quality and user satisfaction, the relationship between use and net benefit and user satisfaction relationship to net benefit, and 3 hypotheses with results rejected namely information quality to use, security relationship to use and security relationship to user satisfaction.